Rhodium‐Catalyzed Enantioselective Isomerization of meso‐Oxabenzonorbornadienes to 1, 2‐Naphthalene Oxides. Issue 22 (20th March 2017) - Yen, Andy; Choo, Ken‐Loon; Yazdi, Shabnam K.; Franke, Patrick T.; Webster, Robert; Franzoni, Ivan; Loh, Charles C. J.; Poblador‐Bahamonde, Amalia I.; Lautens, Mark
Abstract: Herein we describe a rhodium‐catalyzed enantioselective isomerization of meso‐oxabicyclic alkenes to 1, 2‐naphthalene oxides. These potentially useful building blocks can be accessed in moderate to excellent yields with impressive enantioselectivities. Additionally, experimental findings supported by preliminary computations suggest that ring‐opening reactions of bridgehead disubstituted oxabicyclic alkenes proceed through the intermediacy of these epoxides and may point to a kinetically and thermodynamically favored reductive elimination as the origin for the observed enantioselectivities. Abstract : An enantioselective isomerization of bridgehead‐disubstituted meso ‐oxabicyclic alkenes catalyzed by a cationic [Rh(cod)2 ]OTf/( R )‐( S )‐PPF‐P t Bu2 catalyst system is described. The enantioenriched 1, 2‐naphthalene oxide products are potentially useful building blocks in asymmetric synthesis. The involvement of these epoxides as intermediates in asymmetric ring opening reactions of oxabicyclic alkenes is also explored.